2015
DOI: 10.2337/diaspect.28.4.258
|View full text |Cite
|
Sign up to set email alerts
|

American Indian Diabetes Beliefs and Practices: Anxiety, Fear, and Dread in Pregnant Women With Diabetes

Abstract: Diabetes among American Indian (AI) people is a health disparities condition that creates excessive morbidity and mortality. This research delineated culturally constructed models of type 2 diabetes among 97 pregnant women in two large AI nations in Oklahoma. The data analysis of explanatory models of type 2 diabetes revealed the participants’ intense anxiety, fear, and dread related to the condition. The sample was further stratified by combinations of diabetes status: 1) absence of type 2 diabetes (n = 66), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The result was similar to other studies, for example, north American indigenous women with GDM had significant fear and anxiety surrounding the health and well-being of the unborn child and the use of insulin injections. 20 The women in the present study attributed illness and health to the individual factors such as wrong dietary habits, which demonstrated a belief in their own responsibility for their illness and health. 4 This implied that it was possible for these women to take the responsibility for controlling their GDM.…”
Section: Discussionmentioning
confidence: 63%
“…The result was similar to other studies, for example, north American indigenous women with GDM had significant fear and anxiety surrounding the health and well-being of the unborn child and the use of insulin injections. 20 The women in the present study attributed illness and health to the individual factors such as wrong dietary habits, which demonstrated a belief in their own responsibility for their illness and health. 4 This implied that it was possible for these women to take the responsibility for controlling their GDM.…”
Section: Discussionmentioning
confidence: 63%
“…There are complex psychosocial, physiological and practical challenges for breastfeeding among women with GDM. A study among Indigenous women with GDM in the United States reported a high ‘perception of risk’ coupled with low levels of self‐efficacy for preventing cardio‐metabolic disease, 27,28 a combination associated with avoidance behaviour 29 . This suggests recommendations to include confidence‐building (‘strengths‐based’) strategies in breastfeeding support 30 may be particularly important for Indigenous women with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Giving incentives for attendance or having the classes become social events with community support were reccommended. 29 The present study was a preliminary study and it does indicate aspects of the disease where antenatal mothers lack adequate knowledge. However, a future study on the at risk population such pregnant women with high Body Mass Index, previous history of GDM, currently suffering from the same is required for better interpretation of the study results.…”
Section: Discussionmentioning
confidence: 88%